Study of the performance of photomultiplier tubes at high variable counting rates - Yu, Yanhong; Lv, Hongkui; Tariq, Khruam; Liu, Dong; Sheng, Xiangdong; Feng, Cunfeng (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2021)
Over 5000 photomultiplier tubes (PMTs) are being deployed for electromagnetic particle detectors (EDs) for the Large High Altitude Air Shower Observatory (LHAASO) project. The linearity of the PMT signal is optimized using a high dynamic range base. However, the PMT gain and linearity tend to change under various lighting conditions. In this paper, the variations in the gain and linearity of the XP3960 PMT are studied by changing the signal counting rate. The PMT gain increases appreciably at high counting rates due to the voltage redistribution between the dynode stages, resulting in an apparent increase in the linearity of the dynode. The details of the characteristics of PMTs at high counting rates and the corresponding simulations are described. These results show the impact of various counting rates on PMT performances can be ignored in the ED experimental conditions.